PENERAPAN LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK COGNITIVE RESTRUCTURING DALAM MENURUNKAN STRES AKADEMIK SISWA TINGKAT X SMKN 3 CIMAHI - Lala Nuraeni; Samsudin, Asep; Fitri Annisa, Dona (IKIP Siliwangi, 2024)
This study aims to determine the effect of group counseling services with cognitive restructuring techniques in reducing student academic stress which refers to the inability of students to cope with academic stress experienced. Academic stress according to Gadzella & Masten (2005) is the perception of an individual with academic stressors and how they react to academic stressors including reactions to physical, emotional, behavioral and cognitive. The research method used is a mix method design The Explanatory sequence Design using the One Group Pretest-posttest Design. 94 students majoring in fashion at SMKN 3 Cimahi became subjects and 9 students who had been selected as research samples. Sampling according to predetermined criteria according to purposive sampling technique. Purposive Sampling according to Sugoyono (2019) is a sampling technique with predetermined criteria. The measuring instrument used is the academic stress instrument with a reliability test result of 0.878. Paired t test results in a Sig(2-tailed) value containing 0.000<0.05, which means that the alternative hypothesis is accepted and the null hypothesis is rejected, indicating that group counseling using cognitive restructuring techniques has an impact on lowering academic stress in class X students at the Fashion Department of SMKN 3 Cimahi. It is therefore concluded that group guidance services using cognitive restructuring techniques can lower student academic stress.